Justice for Judges in Ukraine: Looking for Peace and Strong Judiciary Institutions in a Sustainable Society - Rudenko, Mykola; Malinovska, Iryna; Kravtsov, Serhij (European Journal of Sustainable Development, 2021)
Regarding the judiciary, the purification and lustration initiatives had been alleged as a beginning of a new stage of radical reformation, appreciated by European institutions. Therefore, in this article we will provide a detailed picture of the lustration of judges in Ukraine from the angle of its procedural guarantees as well as its legal nature; a special focus will be given to issues of efficiency of lustration restrictions, provided by the national legislation as well as its compliance within the European guidelines and Ukrainian Constitution. Lustration of judges will be analyzed regarding ordinary sanctions, enforced upon judges in case of committing disciplinary offences.